The Effects of Statin Therapy on Mean Platelet Volume in Patients with Cardiovascular Diseases - Abduljabbar Abdulrazzaq, Alaa; Hani, Rowshen; Raad Saleh, Aya (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The statins are the excellent therapy for decreasing the lipid and described in about all patients with cardiovascular diseases. It has a strong role in decreasing the morbidity and mortality present with cardiovascular diseases. In recent study, it has been conducted that its major effects is far more than lowering the lipid but also it has a great role in cardiac diseases as the thrombocytopenia and platelet dysregulation also associated in decreasing the cardiac disease effects. This study explained the statin role on the efficiency of the markers and its effect in patients with cardiovascular disease. The platelet counts were examined by the flow cytometer, the samples of blood were collected from patients before and after treatment. The results showed the express of CD62P and CD63 were decrease in patients had the therapy compared to the patients without it. The study concluded that the statin therapy decrease the mean of platelet volume (MPV) in the patients suffer from this diseases.